Odpowiedzi

  • Roma
  • Community Manager
2010-01-09T11:53:52+01:00
Kwadrat sumy (a+b)² = a² + 2ab + b²
kwadrat różnicy (a-b)² = a² - 2ab + b²
sześcian sumy (a+b)³ = a³ + 3a²b + 3ab² + b³
sześcian różnicy (a-b)³= a³ - 3a²b + 3ab² - b³
różnica kwadratów a²-b²= (a-b) * (a+b)
suma sześcianów a³ + b³ = (a+b) * (a² - ab + b²)
różnica sześcianów a³ - b³ = (a - b) * (a² + ab + b²)
kwadrat sumy trzech składników (a+b+c)² = a² + b² + c² + 2ab + 2ac + 2bc

Dużo więcej wzorów znajdziesz pod adresem:
http://pl.wikipedia.org/wiki/Wzory_skr%C3%B3conego_mno%C5%BCenia